Effectiveness Extract Gel of Kemangi Leaves (Ocimum basilicum L.) To The Level of Fibroblast For Incision Wound Healing of Wistar RATS (Rattus norvegicus) - Hendri Poernomo; Setiawan; Yuni Darma Dewi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Wound healing using herbal plants is considered safer than chemical drugs. One of the plants that can be used for wound healing is basil leaves (Ocimum basilicum L.). The purpose of this study was to evaluate the effectiveness of administering basil leaf extract gel on the number of fibroblast cells in the healing process of incision wounds in Wistar rats. Research method: This study used an experimental post-test only control group design using 24 male Wistar rats. The research sample was divided into four groups, namely the negative control group (CMC-Na gel), the group given basil leaf extract gel with concentrations of 70%, 80%, and 90%. In vivo testing was carried out by making an incision wound with a length of 20mm and a subcutaneous depth on the back of the rat. The extract was given twice a day for one week, then decapitation was carried out on the 8th day. Research results: Basil extract gel with concentrations of 70%, 80%, and 90% was effective in healing incision wounds. One Way Anova test showed significant differences between the four groups (ρ<0.05). Conclusion: Basil leaf extract gel with a concentration of 80% is more effective in accelerating wound healing